The role of macrophages in gastric cancer - Zhang, Jiaqing; Hu, Can; Zhang, Ruolan; Xu, Jingli; Zhang, Yanqiang; Yuan, Li; Zhang, Shengjie; Pan, Siwei; Cao, Mengxuan; Qin, Jiangjiang; Cheng, Xiangdong; Xu, Zhiyuan (Frontiers in Immunology, 2023)
As one of the deadliest cancers of the gastrointestinal tract, there has been limited improvement in long-term survival rates for gastric cancer (GC) in recent decades. The poor prognosis is attributed to difficulties in early detection, minimal opportunity for radical resection and resistance to chemotherapy and radiation. Macrophages are among the most abundant infiltrating immune cells in the GC stroma. These cells engage in crosstalk with cancer cells, adipocytes and other stromal cells to regulate metabolic, inflammatory and immune status, generating an immunosuppressive tumour microenvironment (TME) and ultimately promoting tumour initiation and progression. In this review, we summarise recent advances in our understanding of the origin of macrophages and their types and polarisation in cancer and provide an overview of the role of macrophages in GC carcinogenesis and development and their interaction with the GC immune microenvironment and flora. In addition, we explore the role of macrophages in preclinical and clinical trials on drug resistance and in treatment of GC to assess their potential therapeutic value in this disease.